Prioritizing Multi-Interwoven Factors in the Project Management Office Using Delphi and Fuzzy DEMATEL - Abozar Zare Khafri; Abbas Sheikh Aboumasoudi; Shakiba Khademolqorani (Journal of Mathematics)
This study aims to evaluate the cause-and-effect relationships of potential PMO functions at project-oriented organizations. In this research, the Delphi technique was first employed to identify the potential PMO functions, and DEMATEL technique was conducted to evaluate the cause-and-effect relationships. According to the research findings, structure determination and project organization were the most effective PMO functions, whereas counseling and training through PMO was identified as the most important function. Moreover, participation in project implementation through PMO was the most affected function. To improve the PMO performance, project-oriented organizations can focus on effective functions and causes in order to modify and improve them.